2003
DOI: 10.2337/diabetes.52.11.2720
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Hormone–Related Protein Induces Insulin Expression Through Activation of MAP Kinase–Specific Phosphatase-1 That Dephosphorylates c-Jun NH2-Terminal Kinase in Pancreatic β-Cells

Abstract: Parathyroid hormone-related protein (PTHrP) increases the content and mRNA level of insulin in a mouse ␤-cell line, MIN6, and primary-cultured mouse islets. We examined the mechanism of PTHrP-induced insulin expression. The PTHrP effect was markedly augmented by SB203580, a mitogen-activated protein (MAP) kinase inhibitor, and SB203580 itself increased insulin expression extensively, even without PTHrP. Because SB203580 inhibits both p38 and c-jun NH 2 -terminal kinases (JNKs), we investigated the JNKspecific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 58 publications
3
33
0
Order By: Relevance
“…To confirm the involvement of MKP-1 in the attenuating effect of PTH on MAPK phosphorylation, Ro 31-8220, an inhibitor of MKP-1 expression, was administered (14,17,18). We confirmed that Ro 31-8220 inhibited PTH-induced MKP-1 mRNA and protein expression in our model (Figure 7).…”
Section: Effect Of Actinomycin D and Ro 31-8220 On Pth-induced Attenusupporting
confidence: 57%
See 2 more Smart Citations
“…To confirm the involvement of MKP-1 in the attenuating effect of PTH on MAPK phosphorylation, Ro 31-8220, an inhibitor of MKP-1 expression, was administered (14,17,18). We confirmed that Ro 31-8220 inhibited PTH-induced MKP-1 mRNA and protein expression in our model (Figure 7).…”
Section: Effect Of Actinomycin D and Ro 31-8220 On Pth-induced Attenusupporting
confidence: 57%
“…The recent characterization of dual-specific phosphatases as immediateearly gene products (14,15) with rapid transcriptional induction and short half-lives due to rapid degradation by the 26S proteasome (19) made the members of the MKP subclass of this phosphatase family interesting candidate mediators of PTHinduced MAPK dephosphorylation. Indeed, we were able to demonstrate that PTH rapidly and transiently induces gene transcription and protein synthesis of MKP-1 in UMR106-01 osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIT-T15, 10 mmol/l (Santerre et al 1981); INS-1, 11 . 1 mmol/l (Asfari et al 1992); MIN-6, 25 mmol/l (Miyazaki et al 1990, Lilla et al 2003, O'Driscoll et al 2004; and isolated murine islets, 25 mmol/l (Zhang et al 2003), although it should be noted that many researchers culture murine islets in medium containing 5 . 6 or 11 mM glucose.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study was to examine differential regulation of the proteome associated with continuous culture of MIN-6 cells and corresponding loss of GSIS phenotype to enable future development of potential methods whereby relevant beta cell functions could be preserved in long-term culture [14][15][16].…”
Section: Introductionmentioning
confidence: 99%